EDUCATION PROGRAM AND FACILITY IMPROVEMENT FOR PERSONAL HYGIENE AT PONDOK PESANTREN METAL MUSLIM, PASURUAN - Sri Wijayanti Sulistyawati; Dwi Peni Kartikasari; Lynda Rossyanti; Heny Arwati; M. Yasin Fitri Nugroho; Frista Amalia; Bagus Dwi Nugraha; Awwaliyah Azmi Izzati (Universitas Airlangga, 2022)
This community service activity was carried out with the partner of the Muslim Metal Islamic Boarding School, Pasuruan. This activity aims to improve the habits of clean and healthy living behavior (personal hygiene. The activities offered include examination of intestinal parasitic infections for residents of the Muslim Metal Islamic Boarding School, counseling on intestinal parasitic infections and personal hygiene and improvement of PHBS facilities. The counselling given is about various kinds of parasites that cause intestinal infections, transmission of intestinal parasitic infections, and how to prevent intestinal parasitic infections by implementing personal hygiene (PHBS). By knowing about intestinal parasites and how they are transmitted, be expected that they will be able to avoid infection with intestinal parasites by practicing PHBS discipline.